PENETAPAN KADAR FLAVONOID EKSTRAK ETANOL DAUN PACAR KUKU (Lawsonia inermis L.) BERDASARKAN PERBEDAAN CARA PENGERINGAN - Risa Supriningrum; Nurul Fatimah; Sri Nur Wahyuni (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2018)
Leaves of Lawsonia inermis L. are one of the medicinal plants that have antibacterial properties, medicine for wounds on the skin, drugs for inflammation of the knuckles and as a nail dye. One of the active substances contained in the henna leaf is flavonoids. The level of active ingredient extract can be influenced by the way of drying simplicia. The purpose of this study was to determine the levels of flavonoid ethanol extract of girlfriend nail Lawsonia inermis L. leaves based on simplicia drying method. Research conducted was non-experimental research. The stages of the study included collecting samples, determining plants, making simplicia by drying the wind and artificial drying with an oven at 550C, extracting by maceration and determining flavonoid levels by UV-Vis spectrophotometry. The data obtained were analyzed descriptively. Based on the results of the study, obtained flavonoid levels of ethanol extract of leaves on wind-dried drying of 6.15% ± 0.1373 and drying with an oven of 7.37% ± 0.2158.